Tata Kota Islam Ternate: Tinjauan Morfologi dan Kosmologi - Wuri Handoko (Balai Arkeologi Maluku, 2015)
Ternate town, is a thriving Islamic city since 6-17 century AD. Although at that time influenced mainly Portuguese colonial hegemony and the Netherlands, but as a center of Islamic civilization, morphology and cosmology town laid out according to the Islamic concept and local concept. Through archaeological analysis, morphology and cosmological aspects of the town hall is described. For that carried out the archaeological survey in the city of Ternate with trace toponyms ancient city, then through the literature and interviews with sources. Archaeological analysis performed, ie with spatial analysis through data identification features that characterize the ancient city of Islam, as well as contextual analysis by analogy history and local culture. The purpose of this study is to describe the shape and development of the city, as well as cosmological concept underlying the form of urban planning. Results of the study include that component of the city center is characterized by buildings and mosques, kedaton sultan as an orientation center into a city of Ternate characteristics of Islamic civilization. In addition the local characteristics of the town of Ternate is shown by the local cosmological concepts, as well as the division of residential space natives and immigrants. During its development, the urban space is divided into five components, namely component downtown, residential, and commercial economy, burial, and religious.Kota Ternate, adalah sebuah Kota Islam yang berkembang sejak abad ke 6-17 Masehi. Meskipun pada masa itu dipengaruhi pula hegemoni kolonial terutama Portugis dan Belanda, namun sebagai sebuah pusat peradaban Islam, morfologi dan kosmologi kota ditata menurut konsep Islam dan konsep lokal. Melalui analisis arkeologi, aspek ruang morfologi dan kosmologi kota digambarkan. Untuk itu dilakukan survei arkeologi di wilayah Kota Ternate dengan menelusuri toponim-toponim kota kuno, kemudian melalui studi pustaka maupun wawancara dengan narasumber. Analisis arkeologi dilakukan, yakni dengan analisis keruangan melalui identifikasi data fitur yang mencirikan kota kuno Islam, serta analisis kontekstual melalui analogi sejarah dan budaya lokal. Tujuan penelitian ini adalah menggambarkan bentuk dan perkembangan kota, serta konsep kosmologi yang melatarbelakangi bentuk tata kota. Hasil penelitian antara lain bahwa komponen pusat kota yang dicirikan oleh bangunan kedaton sultan dan masjid sebagai pusat orientasi menjadi karakteristik Ternate sebagai kota peradaban Islam. Selain itu ciri lokal kota Ternate ditunjukkan dengan konsep kosmologi lokal, serta adanya pembagian ruang hunian pribumi dan pendatang. Dalam perkembangannya, ruang kota terbagi menjadi lima komponen, yakni komponen pusat kota, pemukiman, ekonomi dan niaga, penguburan, dan keagamaan.